(untitled) (World Bulletin of Public Health, 2022)
This review presents the data of modern scientific research, indicating the involvement of the immune system in the regulation of blood pressure, discusses the mechanisms of neuro-immune regulation of vascular tone, endothelial dysfunction and modulation of cytokine status in the pathogenesis of hypertension. The authors have formulated a conclusion about the predictors of the formation of arterial hypertension and the causal role of immune and inflammatory reactions of the body